Studi Deformasi Rangka Konveyor Batubara dengan Metode Survei Terestris - Virgus Ari Sondang; Ilham Nugraha; Sulaiman Arliansyah; Vergie Ari Sondang (UNIVERSITAS INDO GLOBAL MANDIRI, 2021)
One of the mining activities, especially coal mining, the transfer of material onto ships generally uses conveyors. Conveyors have certain maximum limits for transporting and moving material. In a long period of time and continuous use, the conveyor can be deformed, both vertically and horizontally. The part of the conveyor that allows deformation is the frame that plays a role in supporting the material during the transportation process. This study aims to identify and analyze changes in the position of the conveyor frame through the terrestrial survey method with electronic instruments. The initial data used are benchmarks or tie points in the field whose coordinates are known as the basis for determining the coordinates of control points on the conveyor frame. Observations of the conveyor frame are carried out twice in order to know the position before transportation and after transportation. Observation data processing used Terramodel 10.4 software, and tabular and graphical data visualization using Microsoft Excel. From the observation data processing and conveyor frame deformation analysis, it is concluded that the terrestrial survey method can be applied to observe the conveyor frame deformation. This technique is also able to prove the presence of deformation in the conveyor rate through the shift value, both vertically and horizontally. The vertical position change is obtained from the elevation (Z) component, while the horizontal position change is obtained from the X and Y coordinate axis components. For accuracy the resulting shift value is in millimeters. Keywords : coal, deformation, conveyor, positioning, terrestrial